Homecoming '93 - Grand Isle, Lille, Les Concessions - Dubay, Guy F. (Madawaska, Maine Saint John Valley Publishing Company, 1993)
A town is first of all its people. The people comprise of the cast of characters around which its story nfolds. The first part of this book comprises of the cast of characters. The families, the ancestors from which our heritage is drawn. The French speak of "La Grande Histoire" and "La petite histoire". La petite histoire, the little story, is the more personal one. The first portion of this book is dedicated to just that - the personal matter, the people, the cast of characters.
Keywords: History -- Maine -- Aroostook -- Saint John Valley; Grand Isle, Maine; Grand Isle, Maine; Lille, Maine; Lille, Maine